2019
DOI: 10.1108/itp-09-2018-0421
|View full text |Cite
|
Sign up to set email alerts
|

Continuance interaction intention in retailing

Abstract: Purpose Social media as a competitive marketing tool deliver online platforms for retailers to get closer to their consumers/visitors/shoppers through continued interaction. The purpose of this paper is to scrutinize how customer values (functional, social and experimental) enhance satisfaction, loyalty and identification, and how such relationships, in turn, impact users’ continuance interaction intention. Design/methodology/approach A mixed-method approach was designed to identify the consumers’ perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 124 publications
(199 reference statements)
2
13
0
Order By: Relevance
“…Hence, consistent with prior studies drawn from other contexts (e.g. Moharana and Pattanaik, 2023; An and Han, 2020; Foroudi et al. , 2020), we conceptualized the role of shopping value dimensions on shopping well-being, followed by behavioral responses (chain effects) in an e-retailing setting (see Figure 1).…”
Section: Literature Reviewmentioning
confidence: 81%
“…Hence, consistent with prior studies drawn from other contexts (e.g. Moharana and Pattanaik, 2023; An and Han, 2020; Foroudi et al. , 2020), we conceptualized the role of shopping value dimensions on shopping well-being, followed by behavioral responses (chain effects) in an e-retailing setting (see Figure 1).…”
Section: Literature Reviewmentioning
confidence: 81%
“…The research concluded that perceived value is linked to trust, motivation, satisfaction, service quality, loyalty, positive word of mouth, recommendation, and other positive emotional and behavioral outcomes (Tasci, 2020). Research also confirmed that consumers' functional, social, and experimental values increase satisfaction and loyalty and influence the continuation of the interaction intention (Foroudi et al, 2020). Based on this discussion, the following hypothesis is formulated:…”
Section: Consumer Value's Effect On Brand Loyaltymentioning
confidence: 86%
“…Also, relational value refers to how individuals perceive the benefits of social relations and social well‐being. It can be seen as the improvement of one's self‐concept brought about by consumption (Foroudi et al, 2020). In addition, emotional value is an illustration of the benefits obtained from multimodal elements of purchasing experience, which have internal feelings or affective states.…”
Section: Theoretical Backgroundmentioning
confidence: 99%